2020
DOI: 10.21203/rs.3.rs-74851/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Analysis on Failure Reasons of Quit Smoking Among Smokers in Beijing Communities----based on a cross sectional study

Abstract: Objective To understand the reasons for failure of smoking cessation among community smokers in Beijing, and analyze the influencing factors of the reasons for failure to quit, in order to provide a reference for providing smoking cessation guidance services. Method Based on a cross-sectional study, a one-to-one questionnaire was used. The survey included basic demographic information, tobacco use, and past attempts to quit. And descriptive analysis was used to analyze the distribution of the reasons for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…A study done in Beijing [32] among smokers showed that the main factor for failure of cessation smoking was lack of addiction control and self-willpower which further support lack of self-control as the main barrier to quit smoking. Similarly, we found lack of self-control (53.6%) was voted as the most salient challenge to quit smoking compared to other barriers such as failed assisted smoking (17.8%), peer pressure (14.3%), and stress (10.7%).…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Beijing [32] among smokers showed that the main factor for failure of cessation smoking was lack of addiction control and self-willpower which further support lack of self-control as the main barrier to quit smoking. Similarly, we found lack of self-control (53.6%) was voted as the most salient challenge to quit smoking compared to other barriers such as failed assisted smoking (17.8%), peer pressure (14.3%), and stress (10.7%).…”
Section: Discussionmentioning
confidence: 99%
“…18) In this study, we also found that the management mode is insuffi-cient for patients to quit smoking and improve their dietary habits. In the study of Jin, 19) we found that failure to quit smoking was affected by work or study pressure, the influence of other smokers, and the lack of a smoke-free support environment. Therefore, in the patient's smoking cessation management, we also do more detailed management.…”
Section: Discussionmentioning
confidence: 99%
“…The main variables used to assess smoking cessation outcome, environment support, community tobacco exposure, and social support were derived from survey data from a previous study 18 . The assessment of the environment and social support for tobacco control included latent and observed variables.…”
Section: Methodsmentioning
confidence: 99%